2017
DOI: 10.1094/mpmi-03-17-0054-r
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of CTB7 in the Maize Pathogen Cercospora zeina Overcomes the Lack of In Vitro Cercosporin Production

Abstract: Gray leaf spot (GLS), caused by the sibling species Cercospora zeina orCercospora zeae-maydis, is cited as one of the most important diseases threatening global maize production. C. zeina fails to produce cercosporin in vitro, and in most cases causes large coalescing lesions during maize infection; a symptom generally absent from cercosporin-deficient mutants in other Cercospora spp. Here we describe the C. zeina cercosporin toxin biosynthetic gene cluster. The oxidoreductase gene CTB7 contained several inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 50 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…In contrast, the gene was expressed at a lower level in B73 plants and was not induced by C. zeina in the glasshouse experiment ( Figure 6) (Supplementary Figure S5A). This is consistent with a previous RNAseq study of B73 field-grown plants that did not show differential expression of the gene between leaves with high and low C. zeina content ( Supplementary Table S4) (Swart et al, 2017).…”
Section: The Cml444 Copy Of the Lectinsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, the gene was expressed at a lower level in B73 plants and was not induced by C. zeina in the glasshouse experiment ( Figure 6) (Supplementary Figure S5A). This is consistent with a previous RNAseq study of B73 field-grown plants that did not show differential expression of the gene between leaves with high and low C. zeina content ( Supplementary Table S4) (Swart et al, 2017).…”
Section: The Cml444 Copy Of the Lectinsupporting
confidence: 93%
“…This site is a hotspot for GLS disease. GLS disease and RNAseq data from the B73 plants in this field trial have been reported by Christie et al (2017) and Swart et al (2017) (NCBI GEO accession GSE94442; RRID:SCR_006472); however, the current study used data from the B73-QTL plants.…”
Section: Gls Disease Assessment Of Field-grown Maizementioning
confidence: 99%
See 2 more Smart Citations
“…The initial set of RNA expression features included data from 2-3 replicates of 79 distinct tissue types in the maize inbred B73 (222 total samples) (Stelpflug et al, 2016) and 52 samples from biotic and biotic stress studies of B73 in different labs (Opitz et al, 2014;Makarevitch et al, 2015;Swart et al, 2017) for a total of 274 distinct samples. Normalized (FPKM: fragments per kilobase of exon per million aligned reads) expression values for each gene in each experiment were obtained from (Hoopes et al, 2019).…”
Section: Composition Of the Prediction Variable Datasetmentioning
confidence: 99%